Analisis Onrechmatige Daad Sebagai Kausa Dalam Pembatalan Risalah Lelang - Susilo, Durra Aliefa; Talentina, Gabriella; Andreza, Nadya Puteri; Rani, Riska (Faculty of Law Universitas Islam Indonesia, 2025)
Auction as a legal institution in Indonesia has been regulated since the Dutch East Indies colonial period, with a legal basis that is still valid today. Auction is a way to reach a favourable agreement for the seller by gathering prospective buyers. One of the main problems in the implementation of the auction is the existence of unlawful acts (onrechtmatige daad), which is often the basis for a lawsuit to cancel the auction. In the context of Indonesian law, the determination of onrechtmatige daad against the cancellation of auction minutes refers to Article 1365 of the Indonesian Burgerlijk Wetboek. To determine an action as onrechtmatige daad, conditions such as the existence of an act (daad), fault (schuld), loss (schade), and causality must be fulfilled. The legal process related to auctions also involves legal provisions that regulate the procedures and conditions for implementation, such as the use of appraisal services to determine the limit price, as well as the existence of auction minutes as authentic evidence containing details of the auction process and results.